A Hydrogel-Based Ultrasonic Backscattering Wireless Biochemical Sensing - Nam, Juhong; Byun, Eunjeong; Shim, Hyunji; Kim, Esther; Islam, Sayemul; Park, Moonchul; Kim, Albert; Song, Seung Hyun (Frontiers in Bioengineering and Biotechnology, 2020)
Wireless monitoring of the physio-biochemical information is becoming increasingly important for healthcare. In this work, we present a proof-of-concept hydrogel-based wireless biochemical sensing scheme by ultrasonic backscattering. The sensing system utilizes silica-nanoparticle embedded hydrogel deposited on a thin glass substrate, which presents two prominent interfaces for ultrasonic backscattering (tissue/glass and hydrogel/glass). Under the intervening biological tissue (e.g., pH level), the hydrogel/glass interfaces alter the acoustic properties (e.g. attenuation, reflection) compared to tissue/glass reference. By implementing differential mode of ultrasonic backsacttering, we demonstrate a wireless pH measurements with a resolution of 0.2 pH level change and a wireless sensing range around 10 cm.